Kejadian serangan hama pada Perkebunan Kelapa Sawit (Elaeis guineensis Jacq.) di PTPN IV Sosa - Wardi Siregar; Siti Hardianti Wahyuni; Jumaria Nasution (Journal Agro-Livestock, 2024)
This study identifies and analyzes the occurrence of pest attacks on oil palm plants in the TBM 3 area. Observations were conducted from August 2023 to November 2023 at PTPN IV Sosa, Padang Lawas Regency. The observation began with conducting a survey at the sample collection sites, which are in the oil palm plantation area of PTPN IV Sosa, Padang Lawas Regency. Samples were taken from several areas, namely TBM 1, TBM 2, TBM 3, and TM. The area observed in each section was 1 hectare, with a population of 143 trees in each observation area. The samples used comprised 10% of the total population, resulting in a total of 14 trees observed per area. Observations started from the 10th row at the 5th tree from the roadside, continuing to the 15th tree, and so on, following that pattern. The results indicate that rats, particularly Rattus rattus tiomanicus, are the most significant pests, with an attack percentage reaching 37.16%. In contrast, the incidence of termite attacks is significantly lower, at 2.87%. Although the impact of termite attacks is not as severe as that of rats, continuous monitoring of termite pest attacks remains necessary, especially on younger, more vulnerable plants. These findings highlight the need for effective and sustainable pest control strategies to maintain the health and productivity of oil palm plants.